ENGLISH TEACHING STRATEGIES FOR WRITING ANALYTICAL EXPOSITION TEXT: A CASE STUDY OF THE SECOND-GRADE SENIOR HIGH SCHOOL ENGLISH TEACHERS - Fabiyan Junino Elindika; Nunung Fajaryani; Muhammad Fauzan (Language and Education Journal, 2025)
This qualitative study explores teachers' strategies in teaching analytical exposition text and how to implement these strategies. Data were collected from two second-grade English teachers at SMA Negeri 15 Muaro Jambi through interviews and observations. Data analysis from this study used the theory of Miles and Huberman (1994), which consists of three stages: data reduction, data display, and conclusion drawing. This study found that teachers used three methods to teach analytical exposition text: game usage before learning, the Problem-Based Learning (PBL) Method, and the Jigsaw Method. Both methods were applied in a collaborative approach by forming several groups of students. In the Problem-Based Learning (PBL) method, the teacher gave an issue to a group of students, who later understood the problem and came up with several opinions related to the problem. Finally, they would develop their opinions in the text. The jigsaw method focused more on understanding the material related to the concept of analytical exposition text, where the teacher created cooperative learning to form a complete understanding of the material being studied